Avaliação de híbridos de melão Cantaloupe - Dantas, Django Jesus (Universidade Federal Rural do Semi-Árido, 2008)
The objective of this work was to evaluate cantaloupe melon hybrids with relation to yield, quality and post-harvest aspects of fruits and reaction to leafminer. Were evaluated eight hybrids in two experiments carried out in randomized blocks designs with four replications in Baraúna city, Rio Grande do Norte State. The plot was consisted of one line of 15 meters. The traits assessing were yield, average weight fruit, intern cavity proportion, thickness pulp, firmness pulp, content solids soluble and number of leafmines per leaf. The potential of post-harvest was asses during 28 days in five storage periods (0, 7, 14, 21 and 28 days). During this period was evaluated the traits firmness pulp, content solids soluble, external and internal appearances and weight loss. The hybrids HC-101, HC-121, HC-300 and Hy Mark were promissory because had high yield and estimates of firmness of the pulp, content soluble solids to market.All hybrids were susceptible to leafminer and had shelf-life around of 21 days when stored at temperature of 5ºC and UR 95 ± 5%
Evaluation of Cantaloupe melon hybrids
Keywords: Cucumis melo; Liriomyza sativae; Stored; Resistance; Selection; Cucumis melo; Liriomyza sativae; Armazenameto, Resistência; Seleção; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA